Synthesis and evaluation of 6-(11C-methyl(4-(pyridin-2-yl)thiazol-2-yl)amino)benzo[d]thiazol-2(3H)-one for imaging γ-8 dependent transmembrane AMPA receptor regulatory protein by PET. Issue 4 (15th February 2020) - Yu, Qingzhen; Kumata, Katsushi; Li, Hua; Zhang, Yiding; Chen, Zhen; Zhang, Xiaofei; Shao, Tuo; Hatori, Akiko; Yamasaki, Tomoteru; Xie, Lin; Hu, Kuan; Wang, Gangqiang; et al.
Graphical abstract: Transmembrane AMPA Receptor Regulatory Proteins (TARPs) are a recently discovered family of proteins that modulate the activity of AMPA receptors in the ionotropic glutamate system. TARPs exhibit regional specific expression in the brain, leading to physiological differentiation and modulation of AMPA activity. Herein we develop a novel PET ligand based on a novel TARP subtype γ-8 dependent antagonist and perform preliminary evaluation by PET. Abstract: Transmembrane AMPA receptor regulatory proteins (TARPs) are a recently discovered family of proteins that modulate AMPA receptors activity. Based on a potent and selective TARP subtype γ-8 antagonist, 6-(methyl(4-(pyridin-2-yl)thiazol-2-yl)amino)benzo[ d ]thiazol-2(3H)-one (compound 9 ), we perform the radiosynthesis of its 11 C-isotopologue 1 and conduct preliminary PET evaluation to test the feasibility of imaging TARP γ-8 dependent receptors in vivo .